2008
DOI: 10.3171/jns/2008/109/11/0842
|View full text |Cite
|
Sign up to set email alerts
|

The role of a single nucleotide polymorphism of MDM2 in glioblastoma multiforme

Abstract: Although the MDM2 SNP309 does not portend decreased survival, the increased incidence of the mutant G allele in patients with GBM and its influence on age of onset suggest a potential role in the molecular pathogenesis of GBM, and may be a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
(70 reference statements)
0
16
0
4
Order By: Relevance
“…Support for the model has come from the association of MDM2 SNP309 with differences in the onset of, or the risk for, cancer, as well as survival (2,3,18). For example, earlier ages of onset associated with individuals possessing the G-allele have been demonstrated in softtissue sarcomas (1,19,20), lymphoma (21), leukemia (22), melanoma (23), head, neck, and oral squamous cell carcinomas (24,25), and cancers of the colon (26), breast (21,27,28), bladder (29), ovary (30), brain (31), and liver (32).…”
mentioning
confidence: 99%
“…Support for the model has come from the association of MDM2 SNP309 with differences in the onset of, or the risk for, cancer, as well as survival (2,3,18). For example, earlier ages of onset associated with individuals possessing the G-allele have been demonstrated in softtissue sarcomas (1,19,20), lymphoma (21), leukemia (22), melanoma (23), head, neck, and oral squamous cell carcinomas (24,25), and cancers of the colon (26), breast (21,27,28), bladder (29), ovary (30), brain (31), and liver (32).…”
mentioning
confidence: 99%
“…However, other studies have reported no association between the variant and glioma risk (Wang et al, 2004;Malmer et al, 2005). With respect to MDM2 SNP309, 2 reports have found no correlation with glioma risk (El Hallani et al, 2007;Tsuiki et al, 2007), whereas a study conducted by Khatri et al (2008) has found that allele G may be a low-penetrance susceptibility allele for glioblastoma multiforme.…”
Section: Introductionmentioning
confidence: 78%
“…Among them, studies reported by El Hallani et al (2007) and Tsuiki et al (2007) found no significant association between the MDM2 SNP309 variant and glioma risk. The study conducted by Khatri et al (2008) with 98 glioblastoma multiforme patients and 102 cancer-free controls showed that allele G confers an increased risk of glioma; however, the study showed significant deviation from HWE for the allele distribution in the control group (P < 0.001).…”
Section: Association Between Mdm2 Snp309 and Glioma Riskmentioning
confidence: 99%
See 2 more Smart Citations